Pandemic Uropathogenic Fluoroquinolone-resistant Escherichia coli Have Enhanced Ability to Persist in the Gut and Cause Bacteriuria in Healthy Women. (4th July 2019) - Tchesnokova, Veronika L; Rechkina, Elena; Chan, Diana; Haile, Helen Ghirmai; Larson, Lydia; Ferrier, Kendra; Schroeder, David W; Solyanik, Thalia; Shibuya, Spencer; Hansen, Kelly; Ralston, James D; Riddell, Kim; et al.
Abstract: We report that fluoroquinolone-resistant Escherichia coli are found in feces of 8.8% of healthy women, with most bacteria belonging to pandemic multidrug-resistant ST131- H 30R or ST1193 clonal groups. Moreover, these highly uropathogenic clonal groups demonstrate an especially prolonged gut persistence and high rate of bacteriuria without documented urinary tract infection.